Enrichment, sources and ecological risk mapping of heavy metals in agricultural soils of dhaka district employing SOM, PMF and GIS methods. (January 2021) - Hossain Bhuiyan, Mohammad Amir; Chandra Karmaker, Shamal; Bodrud-Doza, Md; Rakib, Md Abdur; Saha, Bidyut Baran
Abstract: Rapid urbanization and industrial growth have triggered heavy metal contamination in agricultural soil in Dhaka, which is a serious concern for ecological risk and public health issues. In this study, fifty-four soil samples from agricultural lands of Dhaka had been analyzed for assessing accumulation, spatial enrichment, ecological risk and sources apportionment of heavy metals using a combined approach of self-organizing map (SOM), positive matrix factorization (PMF), geographical information system (GIS), and enrichment factor (EF). The results of the enrichment factor, geoaccumulation index and contamination factor index showed that more than 90% of the soil samples were polluted by higher levels of Cr and Cd. The mean pollution load index (PLI) results demonstrated that about 73% of soil samples were moderately polluted by heavy metals. Based on SOM and PMF analysis, four potential sources of heavy metals were found in this study area: (i) agrochemical and sewage irrigation (Cd–As); (ii) combined effect of agriculture, industrial and natural sources (Mn, Co, Ni and Zn); (iii) atmospheric deposition and industrial emission (As–Pb); (iv) chemical and leather tanning industries (Cr). The ecological risk index demonstrated that in terms of Cd content, about 75% of soil samples were moderate to high risk, and 20% were moderate to considerable ecological risk, which was the serious environmental, ecological, and public health concern. The spatial projection of ecological risk values showed that the southern part of Dhaka (Keraniganj Upazila) is a high ecological risk in terms of heavy metal pollution. These risk maps in agricultural soils may play a vital role in reducing pollution sources; so that zonal pollution control, as well as ecological protection, may be achieved in this resource-based agricultural land. Graphical abstract: Image 1 Highlights: Metal content in the agriculture soils in Dhaka are many-folds higher than standard limit. GIS, SOM, PMF, EF provided reliable results for clustering and source apportionment. Ecological risk of Cd posed moderate to high risk in soils of Dhaka. 80% of Cd came from industrial and urban wastewater, and 48% of As from pesticides.